Pre-Service Teachers’ Cognitive and Metacognitive Processes in Integrated STEM Modeling Activity - Mehmet Ali Kandemir; Ilyas Karadeniz (Journal of Education in Science, Environment and Health)
This study was conducted during two educational technology courses in spring term of 2016-2017 academic years. The participants of the study were pre-service teachers who were in mathematics teaching program in a university located at the west part of Turkey. Pre-service teachers were asked to solve a complex problem that requires mathematical model eliciting activities and report their solution. While pre-service teachers were solving the problem and writing their report, they were audio recorded. Additionally, their solutions and reports for problem were collected as data sources. All three various data sources used for triangulation to make the data collection process more reliable. The problem-solving behavior from the study conducted by Kim et al. (2013) was used as the theoretical framework. First, the behavior is classified as cognitive or metacognitive. Then the behavior (either cognitive or metacognitive) is also classified as at individual, social, or environmental levels. Additionally, Lesh Translation Model was used to decide the representations of mathematical content knowledge codes for metacognitive activities. The implications of this study are the developed metacognitive activities for pre-service teachers. Additionally, there is potential usage of technology for the role of metacognition in mathematics education.